The epigenetic basis of evolution. (March 2023) - Spadafora, Corrado
Abstract: An increasing body of data are revealing key roles of epigenetics in evolutionary processes. The scope of this manuscript is to assemble in a coherent frame experimental evidence supporting a role of epigenetic factors and networks, active during embryogenesis, in orchestrating variation-inducing phenomena underlying evolution, seen as a global process. This process unfolds over two crucial levels: i) a flow of RNA-based information - predominantly small regulatory RNAs released from somatic cells exposed to environmental stimuli – taken up by spermatozoa and delivered to oocytes at fertilization and ii) the highly permissive and variation-prone environments offered by zygotes and totipotent early embryos. Totipotent embryos provide a variety of biological tools favouring the emergence of evolutionarily significant phenotypic novelties driven by RNA information. Under this light, neither random genomic mutations, nor the sieving role of natural selection are required, as the sperm-delivered RNA cargo conveys specific information and acts as "phenotypic-inducer" of defined environmentally acquired traits.